(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
At the Agricultural Research Station of the University of Basra’s College of Agriculture, a field experiment was conducted, Karma Ali site during the winter of 2021–2022, Basrah Governorate to study the best level of nitrogen fertilizer, the number of mowing times that give the best yield of green and dry fodder, and some qualitative characteristics of three varieties. The experiment was applied as a split-split plot design according to the randomized complete block design (R.C.B.D) with three replications. The main plots included the number of mowing times (mowing once, twice, three times), which are (C1, C2, C3), and the cultivars occupied the sub-plots (Buraq, Ibaa 99, Ibaa 265), which are symbolized by (V1, V2, V3), while the sub-sub plots included the secondary fertilizer levels are (100, 200, 300) N t ha-1 , symbolized by (N1, N2, N3). The most important results were: Fertilizer level N3 was significantly superior in all studied traits, green and dry forage yield, protein yield, and fiber yield, with a value of (34.69, 11.13, 143.84, 232.20) t ha1 , respectively, in addition, V1 cultivar was significantly superior in the characteristic of green and dry forage yield and protein yield, and fiber, which gave the highest mean (34.33, 10.99, 138.82, 227.40) t ha-1 , respectively. As for the mowing treatment, the mowing treatment for three times C3 was significantly superior in all the studied traits; it gave the highest mean of (46.42, 14.24, 182.45, 299.40) t ha-1 , while the binary interaction between cultivars and the number of mowing times showed a significant effect on yield of green, dry forage and protein yield, fiber yield reached the highest average when class V1 and the number of times mowing C3 (50.45, 15.98, 210.55, 316.80) t ha-1 , respectively